Modified calcium accumulation after controlled cortical impact under cyclosporin A treatment: a 45Ca autoradiographic study - Mirzayan, M Javad; Klinge, Petra M; Ude, Sven; Hotop, Anke; Samii, Madjid; Brinker, Thomas; Korkmaz, Zekiye; Meyer, Geerd J; Knapp, Wolfram H; Samii, Amir (Neurological research (New York), 2008)
As a neuroprotective drug, cyclosporin A (CsA) has been subject of multiple experimental works in traumatic brain injury (TBI) research. It is well known that CsA inhibits calcium (Ca2+) induced mitochondrial permeability transition (mPT). The aim of this study was to investigate the influence of CsA on the alteration of Ca2+ homeostasis after experimental brain injury. Sprague-Dawley male rats (n = 36) with a mean weight of 330 g (280-350 g) were general anesthetized with isofluran through gas mask. The anesthetized animals (n = 24) were subjected to a controlled cortical impact (CCI) over the left parietotemporal cortex using round-tip impounder with a 5 mm diameter at a velocity of approximately 3.7 m/s and a penetration depth of 2 mm. The sham group (n = 12) underwent anesthesia and craniotomy without CCI. In the CCI groups, CsA (n = 12) or vehicle (n = 12) was administered 15 minutes post-injury with a subsequent i.p. injection after 24 hours. Thirty-three hours after injury or sham craniotomy, 45calcium (45Ca) suspended in physiologic saline solution was injected in the left femoral vein. Five hours after isotope administration, animals were killed and the brain was quickly removed and placed in powdered dry ice. Coronal plane sections (20 microm thick) taken every 400 microm from the frontal cortex through the occipital cortex, were exposed to cyclotron films for 14 days at -18 degrees C. Relative optical density was utilized to provide a relative measure of 45Ca accumulation within seven different structures. The difference of 45Ca accumulation (measured by relative optical density) in the CsA group was greater by 30-70% in the following structures compared to vehicle treated traumatized animals: temporal cortex, CA1, anteromedial and posteromedial thalamus (p < 0.05). Post-traumatic 45Ca accumulation is modified under CsA. The crucial neuroprotective effect of CsA might be unrelated to a reduction of post-traumatic Ca2+ accumulation, especially with regard to the importance of Ca2+ as an intracellular messenger governing a large number of cellular functions.